2014
DOI: 10.1177/2053369114557883
|View full text |Cite
|
Sign up to set email alerts
|

Hormone therapy for reproductive depression in women

Abstract: An email survey of patients attending a PMS and Menopause Centre produced 238 patients whose principal presenting symptom was depression. Seventy-seven percent claimed to have had severe or moderate depression, 17% had had at least one psychotic episode and 14% had attempted suicide. Fifty-eight percent had seen a psychiatrist. Seventy-one percent had received antidepressants and 17% had received mood stabilising drugs. Twelve percent had been admitted to a psychiatric hospital and 3.8% had received electrocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…As we noted above, progesterone plays a key role in development, differentiation, and diverse reproductive and non-reproductive functions. Particularly in the CNS, where progesterone regulates various functions such as reproductive behaviour (Gómez-Camarillo et al 2011), learning and memory (Yousuf et al 2017), neuroprotection (Singh, Su 2013), and mood (Conway et al 2007;Dichtel et al 2017;Studd 2014). A.…”
Section: название разделаmentioning
confidence: 99%
“…As we noted above, progesterone plays a key role in development, differentiation, and diverse reproductive and non-reproductive functions. Particularly in the CNS, where progesterone regulates various functions such as reproductive behaviour (Gómez-Camarillo et al 2011), learning and memory (Yousuf et al 2017), neuroprotection (Singh, Su 2013), and mood (Conway et al 2007;Dichtel et al 2017;Studd 2014). A.…”
Section: название разделаmentioning
confidence: 99%
“…The most severe symptom often occur two to three years before the cessation of periods in what is called the menopausal transition or the perimenopause. There are now many scienti ic studies con irming the ef icacy estrogens and certainly the experience of menopausal experts and their patients strongly indicates that estrogens are very effective for this problem should be irst line therapy [5].…”
Section: Menopausal Depressionmentioning
confidence: 99%
“…The major hormone that undergoes such fluctuations in level during these periods is estrogen, and studies have also found that estrogen therapy is effective in the treatment of postnatal depression. 11 , 12 It has also been shown in animal studies that estrogen deprivation led to the decreased expression of serotonin receptors, which could be restored by the administration of estrogen. 13 Estrogens act on target tissues by binding to estrogen receptors.…”
Section: Introductionmentioning
confidence: 99%